2018
DOI: 10.3390/nu10111722
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Consumption of Fructose Induces Behavioral Alterations by Increasing Orexin and Dopamine Levels in the Rat Brain

Abstract: It has been widely described that chronic intake of fructose causes metabolic alterations which can be associated with brain function impairment. In this study, we evaluated the effects of fructose intake on the sleep–wake cycle, locomotion, and neurochemical parameters in Wistar rats. The experimental group was fed with 10% fructose in drinking water for five weeks. After treatment, metabolic indicators were quantified in blood. Electroencephalographic recordings were used to evaluate the sleep architecture a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“…Short-term fructose feeding (10% w/v , fructose solution for five weeks) was shown to alter the sleep-wake cycle in young rats, eliciting wake-promoting effects and reducing the time spent in non-rapid eye movement sleep [ 94 ]. This effect was considered a consequence of the fructose-induced activation of orexinergic neurons in the hypothalamus and of dopaminergic neurons in midbrain regions [ 94 ].…”
Section: Fructose Cognitive Function Aging and Neurodegenerativementioning
confidence: 99%
“…Short-term fructose feeding (10% w/v , fructose solution for five weeks) was shown to alter the sleep-wake cycle in young rats, eliciting wake-promoting effects and reducing the time spent in non-rapid eye movement sleep [ 94 ]. This effect was considered a consequence of the fructose-induced activation of orexinergic neurons in the hypothalamus and of dopaminergic neurons in midbrain regions [ 94 ].…”
Section: Fructose Cognitive Function Aging and Neurodegenerativementioning
confidence: 99%
“…The molecular markers of insulin signaling, as well as AMPKα phosphorylation, where not changed in MIF‐KO mice on fructose diet as compared to individual factors, with the exception of PKCα. These results generally suggest that fructose has beneficial effects on disturbances induced by neuroinflammation in Mif ‐deficient animals, such as behavioral impairments, most likely through increased synthesis of endocannabinoids 95 and dopamine, 96 which has been shown to decrease depression‐like and anxiety‐like behaviors in laboratory models 97 and inhibit cytokine production and expression of adhesion molecules, 98 respectively. Taking into account that it has been shown that brain inflammation is associated with a weakened reward system 99 and that cerebral cortex is a part of the reward system based on signaling via opioid and endocannabinoid receptors, 100 there is a possibility that fructose achieves its role in MIF‐KO mice through the hedonistic aspect of the sugar consumption.…”
Section: Discussionmentioning
confidence: 91%
“…It was reported that a chronic intake of fructose increases the level of orexin A in the hypothalamus and ventral tegmental area [84] (Table 3). This means that hypothalamic orexinergic neurons are activated by this consumption.…”
Section: Othersmentioning
confidence: 99%
“…Central nucleus of the amygdala: orexin A increased gastric motility and palatable food intake Rat [81] Posterior paraventricular thalamus: regulation of hunger-related signals in nucleus accumbens core. Sucrose feeding increases dopamine release in nucleus accumbens shell Rat [82,83] Chronic intake of fructose: increased orexin A level in hypothalamus and ventral tegmental area Rat [84] Feeding (rest phase): decrease in the activation of hypothalamic lateral neurons expressing orexin Rat [85] Decreased orexin A plasma level after four weeks of time-restricted feeding regimen Mouse [86] Sexual dimorphism…”
Section: Feedingmentioning
confidence: 99%